PERMAINAN ULAR TANGGA DAN KARTU PINTAR PADA MATERI BANGUN DATAR - Rora Rizky Wandini; Maya Rani Sinaga (State Islamic University of North Sumatra, 2019)
Playing is near the world of children. The development of the times, science and technology make the purpose of playing not only for mere pleasure, but also need to be inserted educative values in it. The snake ladder game is a game that is liked by elementary school students. Learning mathematics with a snake ladder game media can motivate students to continue learning to develop their abilities by actively involving students in learning. The game of snakes and ladders combined with smart cards can help the students' mathematical learning process to build up flat material. Learning by playing can provide opportunities for students to explore, discover themselves, practice and get a variety of concepts and innumerable understandings and this is where the learning process takes place The teacher is not only limited to transferring knowledge but also guiding students to be skilled in finding concepts of knowledge with experience itself through an inspirational and pleasant learning atmosphere. Thus mathematics subjects which are one of the important sciences that are learned for elementary school students, because they are always used in solving problems in everyday life into pleasant subjects.